Cadmium (Cd) and Lead (Pb) Levels in Oysters Saccostrea cucullata, Water, and Sediment in the Cunda Strait of Lhokseumawe City, Indonesia - Ekamaida, Ekamaida; Kusmana, Cecep; Hariyadi, Sigid; Nurilmala, Mala; Krisanti, Majariana (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Lhokseumawe is a designated as an Economic Growth Center (EGC), making it very susceptible to producing heavy metals.This research aimed to measure the content of lead (Pb) and cadmium (Cd) in oysters (Saccostrea cucullata), water, and sediment in the Cunda Strait, as well as evaluate the relationship between heavy metals and environmental conditions. The experiment was conducted at five stations selected based on considerations of seawater inflow and outflow into the Cunda Strait and existing pollution sources. The results showed that high levels of Pb and Cd with 0.36 and 0.00 mg.kg-1 for S. cucullata, 0.07 and 0.01 mg.kg-1 for water, as well as 7.60 and 0.03 mg.kg-1 for sediment, were found at locations away from the inflow and outflow of the Malacca Strait. The analysis showed a positive pattern in the relationship between Pb metal levels in S. cucullata with water and sediment. This suggested that Pb pollution in S. cucullata came from Pb metal in sediment and water, showing a significant effect on aquatic organisms. However, no clear relationship was found between Cd metal in S. cucullata with sediment and water. The main differences in Pb and Cd between parts were observed in the levels of Pb in water (r= 0.59) and Cd in water (r= 0.71), where higher concentrations were found in central part of the Cunda Strait compared to the southern and northern. Contaminants of heavy metals in S. cucullata, water, and sediment were significantly influenced by temperature, sediment fraction, and organic matter.